A review of the Antillean genus Murgisca Walker, 1863 with descriptions of four new species (Lepidoptera: Pyralidae, Chrysauginae) - V. O. Becker (SHILAP)
Six species of the genus Murgisca Walker, 1863 are recognized, four of them new: Murgisca antillana Becker, sp. n., from Jamaica and Dominican Republic, and M. cubana Becker, sp. n., M. sympatrica Becker, sp. n. and M. taina Becker, sp. n., from Cuba. The genus is restricted to the Antilles, with M. cervinalis Walker, 1863 previously described from the Dominican Republic and M. subductella (Möschler, 1890) from Puerto Rico. Two species are not congeneric and transferred to Lepidomys Guenée, 1852 as L. diplommatalis (Dyar, 1914), comb. n., from Panama and L. pyrophoralis (Hampson, 1916), comb. n., from Peru.